2013
DOI: 10.1177/0363546513497922
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Chronic Exertional Compartment Syndrome in a Physically Active Military Population

Abstract: This study systematically evaluated the epidemiology of CECS among an idealized subset at risk for this condition. Sex, age, race, military rank, and branch of service were all important factors associated with the incidence of CECS in this physically active population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 19 publications
2
73
0
Order By: Relevance
“…It is assumed that American and British recruits do more running, in shorter training courses, whereas Dutch recruits do more marching and their training courses are, on average, longer. The highest reported incidence of MTSS in a military setting was 35% of 124 naval recruits participating in basic military training (BMT) in Australia;4 CECS occurred in US Army soldiers at a rate of 0.49 cases per 1000 person-years (4100 cases diagnosed in 5 years) 11. The relative risk for young female soldiers to sustain an overuse injury is 2.5 in the Dutch military6 and the relative risk for young female soldiers to sustain an overuse injury in the ERLP category has been reported between 1.11 and 3.1 (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that American and British recruits do more running, in shorter training courses, whereas Dutch recruits do more marching and their training courses are, on average, longer. The highest reported incidence of MTSS in a military setting was 35% of 124 naval recruits participating in basic military training (BMT) in Australia;4 CECS occurred in US Army soldiers at a rate of 0.49 cases per 1000 person-years (4100 cases diagnosed in 5 years) 11. The relative risk for young female soldiers to sustain an overuse injury is 2.5 in the Dutch military6 and the relative risk for young female soldiers to sustain an overuse injury in the ERLP category has been reported between 1.11 and 3.1 (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…ACS is a limb-threatening and occasionally life-threatening condition characterized by increased interstitial pressure within an osteofascial compartment, exceeding a critical point and resulting in reduced tissue perfusion and myoneural ischemia ( 8 ). ACS has been reported after heavy exercise, weight lifting, military training, and marathons ( 8 -10 ).…”
Section: Discussionmentioning
confidence: 99%
“…The DMED has been used reliably to quantify incidence and risk factors for various orthopedic conditions. [19][20][21][22][23] The findings have also been shown to translate to a civilian population. 19,20,24,25 We hypothesize that older females in a branch of service with greater physical demands would be predisposed to developing chronic anterior knee pain, in part due to the cumulative occupational demands on the patellofemoral joint.…”
mentioning
confidence: 75%
“…Our findings are concordant with previous studies, which have also shown an increased risk of sport-related injury in athletic females. 22,23,31 A study of professional basketball injuries found that women were 1.6 times more likely than men to sustain a knee injury. 31 In an analysis of 1,784 knee arthroscopies, Lindberg et al found females to have a greater incidence of chondromalacia with concomitant patellar subluxation, while males have a greater incidence of isolated chondral damage with normal patellofemoral kinematics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation